Influences of AR-Supported Simulation on Learning Effectiveness in Face-to-face Collaborative Learning for Physics - Nai Li; Chang, Leanne; Yuan Xun Gu; Duh, H. B-L (2011 IEEE 11th International Conference on Advanced Learning Technologies, 2011)
Augmented Reality (AR), using a mixture of the virtual and physical world, has been recognized as a promising environment for improving the quality of collaboration in educational domains. To identify how an AR-supported simulation affects collaborative learning, this study compared collaborative learning effectiveness between the conditions of AR-supported and traditional face-to-face collaborative learning for Physics. The findings revealed that collaborative use of the AR-supported simulation resulted in higher levels of perceived skill development, self-reported learning and learning interest. The individual learning achievement was also strengthened with the use of AR-supported simulation in collaboration. This study provides empirical evidence for supporting the potential value of AR technology in collaborative learning practices and has implications for research on learning effectiveness evaluation in CSCL.